1983
DOI: 10.2355/isijinternational1966.23.1059
|View full text |Cite
|
Sign up to set email alerts
|

Role of annealing twins for grain refinement in controlled rolling of low carbon microalloyed steel.

Abstract: SynopsisA 0.1 %C-1.35%Mn-0.03%Nb steel was hot rolled in a single pass up to 83 % reduction in thickness at a temperature between 790 °C and 1 050 °C and the deformation state of austenite was examined metallographically in detail. It was found that annealing twins were formed abundantly in the austenite during heating before rolling, or during recrystallization in a high temperature. Rolling at a temperature below the recrystallization temperature of austenite resulted in a severe deformation of these anneali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This implies that plastic accommodation in austenite itself does not promote intragranular ferrite transformation significantly. Since it is known that deformation bands as well as deformed annealing twin boundaries act as preferential nucleation sites within the austenite grain, 19,20) the increase in ferrite nucleation at MnS by hot rolling should be less than the observed increase in intragranular ferrite in Fig. 12(a).…”
Section: Effect Of Strain Field Around Inclusion/precipitate In Austementioning
confidence: 99%
“…This implies that plastic accommodation in austenite itself does not promote intragranular ferrite transformation significantly. Since it is known that deformation bands as well as deformed annealing twin boundaries act as preferential nucleation sites within the austenite grain, 19,20) the increase in ferrite nucleation at MnS by hot rolling should be less than the observed increase in intragranular ferrite in Fig. 12(a).…”
Section: Effect Of Strain Field Around Inclusion/precipitate In Austementioning
confidence: 99%
“…transformation in deep-drawable cold-rolled sheet steels. 1,2) On the other hand, it has been observed that the initial texture hardly changes in microalloyed low-carbon steels with a considerable amount of Mn such as 0.09 mass%C-0.62 mass%Mn-0.03 mass%Nb, 3) 0.1 mass%C-1.35 mass%Mn-0.03 mass%Nb 4) and 0.19 mass%C-1.35 mass% Mn-0.06 mass%Nb 5) controlled-rolled sheet steels, in which martensitic transformation took place during cooling. In these studies, the mechanism was not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…8 It could explain the common tendency, shown in Figures 4.12, 4.17 and 8.2, that the acceleration of transformation is pronounced even with a small amount of deformation in which the increases in the above-mentioned y interfacial surfaces are still gradual. It elevates the A r3> temperature ( 0.11 % C 0.26% Si-1.36% Mn-0.05% Nb -0.04% V-0.004% N Reheated at 1250° C, finish-rolled at temperatures below 800° C and aircooled 13-mm thick plate.…”
Section: Transformation From Nonrecrystallized Ymentioning
confidence: 91%